Cardiogenic shock as the first manifestation of large vessel vasculitis in a young patient: case report (2018)
Background Cardiogenic shock secondary to coronary involvement in large vessel vasculitis (LVV) is an unsuspected finding, even more, when no other vascular territories are compromised and when it constitutes the initial clinical manifestation. This case report illustrates a case in which a complete diagnostic study uncovered this aetiology. Case summary A 33-year-old woman with cough and chest pain who was diagnosed with acute bronchitis returned with worsening dyspnoea, chest pain, and developed cardiogenic shock. The initial differential diagnoses included myocarditis and takotsubo cardiomyopathy (TCM) owing to a positive troponin I, and echocardiogram with left ventricular dilation, dyskinesia in mid-ventricular and apical segments, systolic dysfunction, and functional mitral regurgitation. A cardiac magnetic resonance showed contractility abnormalities resembling the pattern of TCM but lacked the characteristic myocardial oedema. Subsequently, a coronary angiography expected to result without obstructions showed a critical narrowing of the left main coronary artery. Surgical management consisted of a pericardium patch grafted in the stenotic ostium to restore adequate perfusion. The surgical specimens were sent to the pathology laboratory that reported findings compatible with LVV. Four days after the surgical intervention the patient was discharged alive with a complete recovery of left ventricular systolic function. Discussion Chest pain symptoms in a young woman, could be caused by multiple entities, and an ischaemic aetiology from a non-atherosclerotic origin should be kept in mind. A complete study with coronary angiography is crucial to rule out an ischaemic cause even in low-risk groups for atherosclerotic coronary heart disease.